A Cross-Case Analysis of How Faculty Connect Learning in Hybrid Courses - Karen Skibba (Adult Education Research Conference, 2006)
This qualitative, multiple case study analysis found that faculty use hybrid courses to facilitate learning by creating a continuous learning loop between the in-person and online environments. Connecting learning in both environments helps students acquire and integrate new knowledge, extend and refine knowledge, and use knowledge meaningfully.
Keywords: Hybrid Courses; Dimensions of Learning; Case Studies